If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-48=-6f
We move all terms to the left:
-48-(-6f)=0
We get rid of parentheses
6f-48=0
We move all terms containing f to the left, all other terms to the right
6f=48
f=48/6
f=8
| 7x-21=60 | | 1/3n=n-12 | | 7v^2+6v-6=7v | | 213x=2110 | | (7/3)w=21 | | 3x+4+5x-2=180 | | -10=2+s | | 3x(4x+2)=144 | | 45=6z | | 12=25z | | 5x+2(1-x)=2(2x+1)-1x | | y=2035 | | 16=–(x+4)–3(–2–5x) | | 8+2h−4=24 | | -11=v/3 | | 12=4x*8 | | 25+r=-5(2+8r)=6r | | 11+4x=11.5+2x | | –6x–12=24–3x | | -6−4d=-5d−7 | | y=7(X)-3 | | 5x-27+7x-32+9x-8=180 | | (2/3)y=42 | | 42=2/3y | | 3s+71.83=7.99 | | 42=(2/3)y | | 3x=249 | | 7−5+3x−1=5x+3 | | 8x-6=234 | | 10x-4+x+11=180 | | -112=-10m+8 | | 10x-4=x+11 |